2007
DOI: 10.1002/14651858.cd006863
|View full text |Cite
|
Sign up to set email alerts
|

Protein restriction for children with chronic kidney disease

Abstract: Reducing protein intake does not appear to have significant impact in delaying the progression to ESKD in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…Although the effects of a lowprotein diet on the progression of CKD has been the subject of controversy, a protein restriction of 0.6-0.8 g/kg/day is recommended in adult patients with end-stage CKD (Fouque and Aparicio 2007). In contrast, a protein-restricted diet seems to have no significant impact on the progression of CKD in children (Wingen et al 1997;Chaturvedi and Jones 2007). Thus, at the current state of knowledge, recommendations for protein intake in PKU patients with CKD are difficult to establish.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of a lowprotein diet on the progression of CKD has been the subject of controversy, a protein restriction of 0.6-0.8 g/kg/day is recommended in adult patients with end-stage CKD (Fouque and Aparicio 2007). In contrast, a protein-restricted diet seems to have no significant impact on the progression of CKD in children (Wingen et al 1997;Chaturvedi and Jones 2007). Thus, at the current state of knowledge, recommendations for protein intake in PKU patients with CKD are difficult to establish.…”
Section: Discussionmentioning
confidence: 99%
“…Although dietary protein restriction in an animal model of ADPKD was associated with decreased kidney cyst volume and improved renal function [64], similar effects were not observed in ADPKD adult humans, albeit in the setting of advanced structural and functional disease [65]. Regardless, dietary protein restriction is not advocated in growing children including those with chronic kidney disease [66]; however, excessive protein intake should be avoided with underlying renal disease. To date, no specific diet has been studied in or advocated for children with ADPKD.…”
Section: Supportive Treatmentmentioning
confidence: 99%
“…After 2 years of follow-up, neither the primary endpoint (change in creatinine clearance) nor growth was different between the two groups (53). A Cochrane meta-analysis in 2007 concluded that there was uncertainty over the possibility of harm associated with the provision of strict low protein diets on growth in young infants (54).…”
Section: Evidence and Rationalementioning
confidence: 99%